2016
DOI: 10.1051/0004-6361/201629098
|View full text |Cite
|
Sign up to set email alerts
|

Scattered light mapping of protoplanetary disks

Abstract: Context. High-contrast scattered light observations have revealed the surface morphology of several dozen protoplanetary disks at optical and near-infrared wavelengths. Inclined disks offer the opportunity to measure part of the phase function of the dust grains that reside in the disk surface which is essential for our understanding of protoplanetary dust properties and the early stages of planet formation. Aims. We aim to construct a method which takes into account how the flaring shape of the scattering sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
196
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(215 citation statements)
references
References 41 publications
17
196
1
1
Order By: Relevance
“…Future CO emission lines observations with a better angular resolution and sensitivity, perhaps using higher rotational lines, will help to constrain the velocity structure in the cavity. This case can be compared to the disk HD 135344B which also probably has a mildly inner warped disk (Stolker et al 2016). It is different of the binary system HD 142527, which contains a strongly warped disk, by 70…”
Section: Disk Dynamic: An Inner Warped Disk?mentioning
confidence: 93%
See 1 more Smart Citation
“…Future CO emission lines observations with a better angular resolution and sensitivity, perhaps using higher rotational lines, will help to constrain the velocity structure in the cavity. This case can be compared to the disk HD 135344B which also probably has a mildly inner warped disk (Stolker et al 2016). It is different of the binary system HD 142527, which contains a strongly warped disk, by 70…”
Section: Disk Dynamic: An Inner Warped Disk?mentioning
confidence: 93%
“…With the the possible presence of a warped inner disc in MWC 758 projecting shadows in the outer regions, this possibility has not to be discarded. Indeed, the two other disks which are known to feature an inner warped disk, HD 135344B and HD 142527, also have a large cavity and spirals (Stolker et al 2016;Christiaens et al 2014;Casassus et al 2015a). It is also still unclear if a planet inside the cavity, with a non-coplanar or eccentric orbit, might produce such spirals.…”
Section: Possible Scenariosmentioning
confidence: 99%
“…(10) should be observable in such images. During the preparation of this manuscript, Stolker et al (2016) reported a curved shadow in the HD 135344 B disk and determined that it is well fitted by the flat-disk shadow as described by Eq. (1).…”
Section: Observabilitymentioning
confidence: 99%
“…Grady et al 2001;Hashimoto et al 2011;Boccaletti et al 2013;Grady et al 2013;Avenhaus et al 2014;Benisty et al 2015;Wagner et al 2015;Stolker et al 2016) and there is much interest in understanding their origins, which might be perturbations by giant planets, disk-envelope interactions, instabilities, or other phenomena. We present a new mechanism for creating scattered-light spirals: the finite speed of light can cause a shadow from the inner disk to morph into a spiral, with properties determined by the disk and viewing geometry, and the orbital motion of the shadowing clump.…”
Section: Introductionmentioning
confidence: 99%
“…Recent multi-wavelength observations of protoplanetary disks revealed astonishing structures, such as concentric dust rings, spiral arms, and asymmetries (e.g., van der Marel et al 2013; ALMA Partnership et al 2015;Casassus et al 2015;Andrews et al 2016;de Boer et al 2016;Ginski et al 2016;Pérez et al 2016;Stolker et al 2016;Fedele et al 2017). These observations suggest that significant evolution has taken place and that probably planets have already imprinted their existence in the parental disks.…”
Section: Introductionmentioning
confidence: 99%